2010
DOI: 10.1186/1471-2296-11-22
|View full text |Cite
|
Sign up to set email alerts
|

Impact of community-acquired paediatric rotavirus gastroenteritis on family life: data from the REVEAL study

Abstract: BackgroundRotavirus is the leading cause of acute gastroenteritis (AGE) and the most frequent cause of severe diarrhoea in children aged less than 5 years. Although the epidemiology of rotavirus gastroenteritis (RVGE) is well documented, there are few data on the impact of RVGE on the families of affected children.MethodsData associated with the burden of RVGE, including number of working days lost, levels of parental stress, the need for alternative childcare arrangements and additional nappies used, were ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 16 publications
2
31
0
4
Order By: Relevance
“…9 This has been documented by epidemiological data, but the consequences have not been fully investigated. 10,11 Overcrowding leads to high turnovers, with consequent potential for premature discharge and high readmission rates. [12][13][14][15] Over-stressed conditions for staff may be associated with high sickness rates requiring recruitment of temporary personnel, which in turn may be associated with a risk of incorrect diagnosis and/or treatment.…”
Section: Introductionmentioning
confidence: 99%
“…9 This has been documented by epidemiological data, but the consequences have not been fully investigated. 10,11 Overcrowding leads to high turnovers, with consequent potential for premature discharge and high readmission rates. [12][13][14][15] Over-stressed conditions for staff may be associated with high sickness rates requiring recruitment of temporary personnel, which in turn may be associated with a risk of incorrect diagnosis and/or treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Viruses, including rotavirus (RV), norovirus (NoV), enteric adenovirus 40/41 (AdV) and astrovirus (AsV) have been shown to be important causes of acute diarrhea in children during the early years of life [8][9][10][11]. RV and NoV are considered the most important causative agents of viral gastroenteritis [12,13] and surveillance studies have demonstrated that RV is one of the most common causes of diarrhea among children seeking hospital care for their illness [14]. RV infections are responsible for millions of childhood hospitalizations and thousands of potentially preventable deaths in developing countries each year [15].…”
Section: Introductionmentioning
confidence: 99%
“…15 The mean number of working days lost ranged from 2.3 d (France, hospital setting) to 7.5 d (UK, primary-care setting), which constituted a considerable economic burden from a societal perspective. 15 Additional childcare arrangements were required in up to 21% of episodes in this study, representing an economic burden on families affected.…”
Section: Care Giver Burden Associated With Childhood Diseasesmentioning
confidence: 99%
“…15 The mean number of working days lost ranged from 2.3 d (France, hospital setting) to 7.5 d (UK, primary-care setting), which constituted a considerable economic burden from a societal perspective. 15 Additional childcare arrangements were required in up to 21% of episodes in this study, representing an economic burden on families affected. However, while there is some evidence demonstrating a high burden to care givers, there is a need for further research data to more accurately quantify the economic impact of this, as this can have a considerable impact on the findings of cost-effectiveness analyses.…”
Section: Care Giver Burden Associated With Childhood Diseasesmentioning
confidence: 99%